The Resettlement Experiences of Oromo Women Who Entered Canada as Refugees - Yousuf, Biftu; Berry, Nicole S. (Refuge: Canada’s Journal on Refugees, 2021)
A growing body of literature shows that gender-based experiences produce different circumstances for men and women who become refugees and thereafter. This article sought to contribute to this literature by investigating the challenges faced by Oromo women who have immigrated to Canada as refugees. Toward this end, we interviewed six Oromo women in Western Canada regarding what led them to leave Ethiopia, their experiences as refugees seeking asylum, and their struggles with resettlement and integration. The findings reveal that Oromo women share the challenges endured by their male counterparts, but also are victim of gender-based subjugation at each stage of emigration.